Spiritual Therapy-Based Videos Combined with Lecture Methods to Increase Religiosity Among Older People Living in Nursing Homes - Helena Patricia; Emira Apriyeni; Dwi Christina Rahayuningrum (Universitas Malahayati Lampung, 2023)
ABSTRACT Among the stages of human development, aging is a natural phenomenon. Transferring elderly individuals to nursing homes is a crucial to protect and promote the health of the elderly residents because they lack family support. So, a spiritual meaning system is needed that can assist people in handling stressful situations. One way to assess spiritual health in older people is to measure their level of religiosity. A person's religiosity can be increased by doing spiritual therapy. Sabai Nan Aluih Sicincin Nursing Homes is one of the nursing homes in West Sumatra. One hundred ten older people live in orphanages with limited staff, especially health workers and therapy counsellors. Based on direct observations during the initial survey, it was found that there were several problems with older people feeling anxious, uneasy, often sad, lonely, empty of mind, and happy to be alone. The present study aimed to investigate the effect of religious therapy-based videos combined with lecture methods on increasing religiosity among older people in nursing homes. The performance of spiritual treatment using videos combined with the lecture method combines two main approaches in delivering psychotherapy: the audiovisual and direct lecture. The findings are increase in the average score on the religiosity scale when filling out the pretest and post-test questionnaires, namely 24.75 at the pretest, rising to 31.50 at the post-test. The activity went well, where older people could follow the event's direction well, and no participants left the place during the exercise. Therefore, it is hoped that nursing homes can learn techniques for implementing this therapy through video tutorials provided by the community service implementing team. Keywords: Spiritual Therapy, Videos Combine with Lecturer Methods, Religiosity, Older People, Nursing Homes.